Personal information and public health: Design tensions in sharing and monitoring wellbeing in pregnancy. Issue 135 (March 2020) - Doherty, Kevin; Barry, Marguerite; Belisario, José Marcano; Morrison, Cecily; Car, Josip; Doherty, Gavin
Highlights: Sharing personal data in public health is very different from the closed-circle of personal data use. Sharing data has both pragmatic (time, workload etc.) and psychosocial (confidence, competence, connectedness etc.) implications for care. Health professionals must balance care for the individual against the wellbeing of the patient population. Women prefer reflective and conversational, rather than directive or transactional, feedback. Designers are advised to focus on strategies to support negotiation, navigate uncertainty, and realise a shared practice of wellbeing. Abstract: Mobile technologies are valuable tools for the self-report of mental health and wellbeing. These systems pose many unique design challenges which have received considerable attention within HCI, including the engagement of users. However, less attention has been paid to the use of personal devices in public health. Integrating self-reported data within the context of clinical care suggests the need to design interfaces to support data management, sense-making, risk-assessment, feedback and patient-provider relationships. This paper reports on a qualitative design study for the clinical interface of a mobile application for the self-report of psychological wellbeing and depression during pregnancy. We examine the design tensions which arise in managing the expectations and informational needs of pregnant women, midwives, clinical psychologists, GPs and other health professionals with respect to a broad spectrum of wellbeing. We discuss strategies for managing these tensions in the design of technologies required to balance personal information with public health.